Hama dan Penyakit pada Tanaman Cabai Rawit yang Dibudidayakan di dalam Polybag - Wince Amsyah Natalia Zai; Putri Khide Talenta Mendrofa; Ardianus Berkat Saleh Waruwu; Putra Hidayat Telaumbanua; Ayler Beniah Ndraha (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2025)
This study examines the main pests and diseases that attack cayenne pepper (Capsicum frutescens) plants grown in polybags. In Indonesia, this crop is in high demand for both household and industrial use. Nonetheless, farmers often face challenges from pest and disease attacks, including anthracnose, fusarium wilt and stem rot, leading to reduced yields. The methodology used was a literature review covering various sources related to cayenne pepper. Findings show that important diseases such as anthracnose can reduce yields by up to 80%, while pests such as fruit flies can cause chili fruits to drop prematurely before harvest. Effective pest and disease management is essential to increase the productivity of cayenne pepper cultivated in polybags.